2021
DOI: 10.3390/cancers13164038
|View full text |Cite
|
Sign up to set email alerts
|

Aptamer-Functionalized Gold Nanoparticles for Drug Delivery to Gynecological Carcinoma Cells

Abstract: Cervical cancer is one of the most common cancers and is one of the major cause of deaths in women, especially in underdeveloped countries. The patients are usually treated with surgery, radiotherapy, and chemotherapy. However, these treatments can cause several side effects and may lead to infertility. Another concerning gynecologic cancer is endometrial cancer, in which a high number of patients present a poor prognosis with low survival rates. AS1411, a DNA aptamer, increases anticancer therapeutic selectiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
(64 reference statements)
4
16
0
Order By: Relevance
“…In cervical cancer, one study ( Lopes-Nunes et al, 2021 ) covalently bound the AS1411 aptamer with AuNPs as the carrier of acridine orange derivative (C8) or imiquimod (IQ) ( Figure 3A ). Upon final synthesis, the nanoparticles possess characteristics that are suitable for drug applications, such as small size, negative charge, and effective release of drugs.…”
Section: Aptamer-conjugated Aunps For Cancer Therapeuticsmentioning
confidence: 99%
“…In cervical cancer, one study ( Lopes-Nunes et al, 2021 ) covalently bound the AS1411 aptamer with AuNPs as the carrier of acridine orange derivative (C8) or imiquimod (IQ) ( Figure 3A ). Upon final synthesis, the nanoparticles possess characteristics that are suitable for drug applications, such as small size, negative charge, and effective release of drugs.…”
Section: Aptamer-conjugated Aunps For Cancer Therapeuticsmentioning
confidence: 99%
“…Although AS1411 has been withdrawn from clinical trials at present, the development of AS1411 nanomaterial complexes as targeted molecules can make significant contributions to the research related to cancer treatment, so the research on its structural optimization and the role of its nanomaterial is still very hot [ 176 , 249 257 ]. The following new studies of AS1411 have been reported in recent 6 months, which proves that although AS1411 has been developed for many years, the functional development of its nanocomposites is still a hot research issue at the present stage.…”
Section: The Latest Research On As1411mentioning
confidence: 99%
“…Other functional molecules can be further connected to the conjugates. [150,151] Gold nanoparticles absorb visible light due to the excitation of surface plasmon resonance, and the absorption wavelength depends on particle size. Gold nanorods are still more eminent for DDS, since their absorption peaks cover near-infrared region and overlap with the transmission window of biological tissues.…”
Section: Non-dna Auxiliaries To Accomplish Additional Functions For Ddsmentioning
confidence: 99%